No place for magic : book four in the tales of the frog princess - Baker, E. D. (New York : Bloomsbury, 2006)
Emma and Eadric travel to Upper Montevista to ask his parents to bless their upcoming marriage and discover that Eadric's younger brother has been kidnapped by trolls.
Booklist, December 2006.
Horn Book, April 2007.
Voice of Youth Advocates (V.O.Y.A.), June 2007.
5.4
3-6
870L
Keywords: Magic -- Fiction; Witches -- Fiction; Trolls -- Fiction; Humorous stories; Fantasy; Magic -- Fiction; Witches -- Fiction; Trolls -- Fiction; Humorous fiction; Fantasy fiction; Magic -- Fiction; Witches -- Fiction; Trolls -- Fiction; Fantasy; Humorous stories